Optimization of a Marine Fish Release Strategy: A Case Study of Black Sea Bream Acanthopagrus schlegelii in the Zhanjiang Estuary, Northern South China Sea - Zhang, Shenzeng; Lin, Lin; Wang, Xuefeng (Frontiers in Environmental Science, 2021)
The release strategy (choice of the species and locations stocked, releasing mode, and stocking size and times) is an important part of quantitative evaluations of marine fish stock enhancement, while optimization of the release strategy can contribute to assess the stocking success intended to alleviate declining fishery resources and to increase the income of fishers. In this study, a typical fish species released in the northern South China Sea, black sea bream Acanthopagrus schlegelii, was taken as the research object. The biological characteristics of this sparid were determined from samples collected from waters in the Zhanjiang estuary during June, July, and September 2020 to April 2021, and the data were applied to estimate its length frequency and its growth parameters using the ELEFAN I run in FiSAT II. We then simulated and evaluated the stocking effects of five scenarios under different release strategies, while assuming a fixed total quantity of released fish and a constant of mortality rate at different life stages. The results showed that (1) the breeding season of black sea bream in this region is mainly from December to March of the next year, which is also the period when most significant sexual reversal in this species occurs, and (2) the relationship between standard length and weight in black sea bream is W = 5.092 × 10–5L2.906, L∞ = 54.39 cm, K = 0.15, and t0 = −0.967. (3) The recommended period to release black sea bream in Zhanjiang waters is from June to October. It appears more productive if the total quantity of fish released can be divided into two batches. The growth potential of released juvenile fish in this study was evaluated based on a density-dependent theory, and the stocking effect of released stocks was simulated with the consideration for biological parameters and field sampling technique. This study provides a reference for the optimization of fish release strategies in coastal waters.